2013
DOI: 10.1002/prca.201300010
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of a robust glycodiagnostic agent supported by multiple lectin‐assisted glycan profiling

Abstract: The multiple use of lectin-assisted glycan profiling enabled us to construct a reliable sandwich assay kit for monitoring liver fibrosis in patients with viral hepatitis. This will assist in the development pipeline for other glycodiagnostic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(102 citation statements)
references
References 15 publications
1
101
0
Order By: Relevance
“…27 However, it is apparent that WFA + -M2BP more specifically reflects the progression of fibrosis and thus is a suitable novel surrogate for LB in chronic liver diseases. 19,28 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27 However, it is apparent that WFA + -M2BP more specifically reflects the progression of fibrosis and thus is a suitable novel surrogate for LB in chronic liver diseases. 19,28 …”
Section: Discussionmentioning
confidence: 99%
“…19 Measured analyte levels, conjugated to Wisteria floribunda agglutinin, were indexed using the following equation: …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measured values of WFA + -M2BP conjugated to WFA were indexed with the values obtained using the following equation: Here, [WFA + -M2BP] sample represents the WFA + -M2BP count of the serum sample (PC, positive control; NC, negative control). The positive control was supplied as a calibration solution preliminarily standardized to yield a COI value of 1.0 [26]. …”
Section: Methodsmentioning
confidence: 99%
“…Several reports performed with proteome analysis have identified Mac-2 binding protein as a potential marker of liver fibrosis progression [2225]. Kuno et al were the first to report that a rapid and simple glycan-based immunoassay for WFA + -M2BP can quantify fibrosis [20,26]. On the other hand, we reported that AFP and WFA + -M2BP values are noninvasive predictive markers for the development of HCC in patients with HCV [27,28].…”
Section: Introductionmentioning
confidence: 99%